White and Black adolescent females differ in profiles and longitudinal patterns of alcohol, cigarette, and marijuana use - Chung, Tammy (2013)
Emerging research suggests that White youth are more likely to show continuity of alcohol use in the year following drinking onset, compared to Black youth. Little is known, however, regarding racial differences in year-to-year continuity of alcohol, cigarette, and marijuana use during adolescence, particularly among females, who are at greater risk for certain substance-related harm than males. This study used latent class/transition analysis to identify profiles of past year alcohol, cigarette, and marijuana use at ages 13–17 in a community sample of 1076 adolescent females (57% Black, 43% White). Three profiles of past year substance use were identified in separate analyses by race: “no use,” “alcohol only,” and “polydrug use.” Although similar labels describe the profiles, the probability of endorsing use of a particular substance for a given profile differed by race, precluding direct comparison. Latent transition analyses of five annual waves covering ages 13–17 indicated that an intermittent pattern of use (e.g., use in one year, but not the next) was relatively low at all ages among White girls, but among Black girls, an intermittent pattern of use began to decline at age 15. Among Black girls, conduct problems at age 12 predicted substance using profiles at age 13, whereas among White girls, intentions to use alcohol and cigarettes at age 12 predicted substance using profiles at age 13. Racial differences in girls’ substance use profiles suggest the potential utility of culturally-tailored interventions that focus on differences in risk for specific substances and relatively distinct early patterns of use.